2019
DOI: 10.1016/j.foodchem.2018.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant response of cucumber (Cucumis sativus) exposed to nano copper pesticide: Quantitative determination via LC-MS/MS

Abstract: Targeted metabolomics aims to provide a new approach to investigate metabolites and gather both qualitative and quantitative information. We describe a protocol for extraction and analysis of plant metabolites, specifically 13 secondary metabolites (antioxidants) using liquid chromatography coupled to triple quadrupole mass spectrometry (LC-MS/MS), with high linearity (R2 > 0.99) and reproducibility (0.23-6.23 R%) with low limits of detection (>0.001 ng/mL) and quantification (>0.2 ng/mL). The protocol was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…The increase in the antioxidant activity induced by the application of Cu NPs found in the present work reaffirms the conclusions by Fu et al and Huang et al [55,56], who proposed that NPs stimulate the concentration and activity of antioxidants. This biostimulation may be due to the interaction of NPs with intracellular structures as a result of their high reactivity and ease of penetrating cell barriers [26] by endocytosis, pore formation, transport proteins, or plasmodesmata [27].…”
Section: Resultssupporting
confidence: 93%
“…The increase in the antioxidant activity induced by the application of Cu NPs found in the present work reaffirms the conclusions by Fu et al and Huang et al [55,56], who proposed that NPs stimulate the concentration and activity of antioxidants. This biostimulation may be due to the interaction of NPs with intracellular structures as a result of their high reactivity and ease of penetrating cell barriers [26] by endocytosis, pore formation, transport proteins, or plasmodesmata [27].…”
Section: Resultssupporting
confidence: 93%
“…[41]. These classes of phenolic acids were also reported in melon by Mallek-Ayadi et al [42] and other studies on Cucumis sativus showed the same presence of this class of compounds [43].…”
Section: Putative Metabolite Identification By Uplc-qtof-mssupporting
confidence: 67%
“…Advances in QqQ in single reaction monitoring (SRM) mode allows robust absolute quantification of metabolites with high sensitivity and selectivity, even at trace levels with relatively high throughput. Column chemistry and its retention mechanism are extremely critical for targeted analysis of metabolites using LC-MS; and hence, reverse phase (RP) and hydrophilic interaction liquid chromatography (HILIC) are used to cover broad range of metabolites with contrasting polarity (Huang et al, 2018(Huang et al, , 2019Jorge et al, 2016). Targeted analysis is particularly useful as a follow up from untargeted analysis, in order to focus on specific metabolic pathways or testing application of ENMs in pathogen defense, nutrient acquisition, photosynthetic efficiency or productivity.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Here, we have reviewed fifteen publications that have applied untargeted metabolomics to elucidate underlying mechanisms in plants exposed to various metal/metal oxide nanoparticles (nCu, nCu(OH) 2 , nCeO 2 , nFe 3 O 4 , nTiO 2 , nSiO 2 , nAg and nCdO,) by acute or chronic application via root or leaves (Table 1). A few studies have also employed targeted metabolomics on selected group of metabolites, based on the findings from untargeted analyses (Huang et al, 2018(Huang et al, , 2019Majumdar et al, 2019).…”
Section: Application Of Metabolomics For Elucidating Mechanisms Of Enmentioning
confidence: 99%